2015
DOI: 10.2147/jpr.s88207
|View full text |Cite
|
Sign up to set email alerts
|

Migraine: treatments, comorbidities, and quality of life, in the USA

Abstract: This study sought to characterize the experience of stress, treatment patterns, and medical and disability profile in the migraineur population to better understand how the experience of migraines impacts the social and psychological functioning of this group. A 30-minute self-report survey was presented via a migraine-specific website with data collection occurring between May 15 and June 15, 2012. Recruitment for the study was done through online advertisements. In total, 2,907 individuals began the survey a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 20 publications
6
58
0
Order By: Relevance
“…24 Here, we found that high BDI, HADS anxiety, and HADS depression scores were associated with higher migraine frequency (linear trends). Schürks et al showed that RLS prevalence in migraine ranged from 8.7% to 39.0% and identified RLS as an important comorbidity of migraine.…”
Section: Discussionmentioning
confidence: 52%
“…24 Here, we found that high BDI, HADS anxiety, and HADS depression scores were associated with higher migraine frequency (linear trends). Schürks et al showed that RLS prevalence in migraine ranged from 8.7% to 39.0% and identified RLS as an important comorbidity of migraine.…”
Section: Discussionmentioning
confidence: 52%
“…Massage therapy use for those with migraine ranged from 2.0 to 29.7% (mean: 15.6%) within the general population [49, 50, 71] and from 10.1 to 56.4% (mean: 33.9%) within headache-clinic populations [53, 54, 72, 73]. Massage/acupressure use for those reported as headache within headache/pain clinic patient populations ranged from 12.0 to 54.0% (mean: 32.5%) [5860, 70].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, providers who treat individuals with comorbid migraines and nicotine addiction should educate their patients about the migraine frequency-smoking connection and provide resources to help them quit. Moreover, providers should refer those patients and patients with a lower sense of control over their migraine to a psychologist to increase their self-efficacy, particularly in the area of pain management [25][26][27]. By only providing medications to those patients, providers are inadvertently enabling and feeding the patient's external locus of control around medications, headaches, and treatment options as well as tacitly approving of the smoking behaviors that are causing harm and are linked to increased migraine frequency.…”
Section: Implications For Interventionsmentioning
confidence: 99%